Penerapan Psikologi Islam dalam Praktik Profesi Psikolog Muslim - Yulia Hairina; Mubarak Mubarak (Jurnal Psikologi Islam dan Budaya, 2020)
This research aims to describe the application of Islamic Psychology in the practice of Muslim psychologists and the obstacles in its application. This study uses a qualitative approach for taking respondents using purposive sampling techniques. There are twenty respondents in this study. The method used in collecting data from this study is the interview and Focus Discussion Group. This study found that the understanding of Islamic Psychology was quite diverse, but in essence, an approach that used the Qur'an and Hadist was the primary reference source. Its application, including the psychological services, and the process of counseling and therapy were carried out by integrating psychology and Islam. The cases also handled varied, not limited to severe or mild cases. The challenges were related to the ability of the psychologists and the acceptance of the clients.